(untitled) (Publicaciones en Ciencias y Tecnología, 2022)
The article presents the findings of a systematic review immersed in the literature, focused on identifying the main elements of Technology Management in chemical industries. A total of 556 scientific articles were obtained using online scientific search engines. The analysis was exploratory/descriptive using the cocitation context analysis method, based on the perspective of the academic genealogy retrospective literature, statistics and distribution, making use of VOSviewer® co-occurrence to reflect the link chain of common thread, whose result denoted 30 binding terms to the study area, which are: Cost, gap, identification, implementation, improvement, policy, products, production, six sigma quality system, stakeholders, sustainable development, technique, capacity, collaboration, competitive advantages, customers, innovation, manufacturer, supplier, flexibility, integration, manufacturing companies, performance, relationships, supply chain management, adoption, data and uncertainty. In conclusion, the most relevant terms of Technology Management are obtained from the systematic review in the period 2011 to 2021, as well as these terms were grouped through data mining, obtaining 5 broadly defined clusters. Additionally, the main terms with propensity capacity and/or trends since 2018 are highlighted.